A CONTRIBUTION TO THE KNOWLEDGE OF THE PARASITIC WASPS SUBFAMILY EULOPHINAE (HYMENOPTERA: EULOPHIDAE) OF JAVA, INDONESIA - Rosichon Ubaidillah (Treubia, 2007)
A study of the eulophid wasp subfamily Eulophinae was carried outbetween 2004-2006 in Java and the adjacent small islands (e.g. Bali, Madura,Nusa Barong, Sempu, Nusakambangan and Krakataus) to determine theEulophinae fauna of Java. As a result, 23 genera and 86 species, belonging tothe subfamily Eulophinae were found, from those 11 genera and 35 species arenew record for Java and Indonesia. Key to genera, generic diagnostic and theavailable eulophine species to the islands are presented.